Alih Fungsi Pesisir Pascareklamsi dan Implikasinya terhadap Marginalisasi Nelayan di Pulau Serangan, Denpasar - Nyoman Suryawan (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
This article analyzes process of marginalization of Serangan Island community in Denpasar, Bali, as a result of the island’s coastal reclamation project began in the early 1990s. The study uses qualitative research methods whereas data collection techniques included participant observation, in-depth interviews, and documentation study. Data were critically analyzed applying some cultural studies theories. Results of the study are as follows. First, the form of marginalization of fishermen looked in economic marginality, and urgency in the use environment. Second, there were external and internal factors that cause marginalization. External factors included the role of government through product legislation in force, the involvement of investors through reclamation, and utilization of coastal areas for the benefit related to tourism and other business services. Internal factors caused by low human resource fisherman seen from his education and lifestyle consumerism. Third, the marginalization of the fisherman has a meaning of its own that is concerning the meaning of existence, the meaning of solidarity, and the meaning of life struggle.